2021
DOI: 10.1136/bcr-2020-239664
|View full text |Cite
|
Sign up to set email alerts
|

Rare, post-periodontitis spondylodiscitis caused byFusobacterium nucleatumin a patient with multiple sclerosis: challenge of diagnosis and treatment

Abstract: Fusobacterium nucleatum is part of the commensal flora of the oral cavity, frequently associated with periodontal infections. We describe the case of a 49-year-old woman, on immunsuppressive therapy for multiple sclerosis, who presented with a 3-month history of debilitating back pain. She had a recent episode of periodontitis, and was under regular dental review. Her MRI scan demonstrated findings suggestive of L2–L3 spondylodiscitis. Her CT-guided biopsy yielded negative cultures and the patient failed two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Of the 27 identified publications, the authors found 15 published reports of discitis or NVO attributable exclusively to F. nucleatum [5][6][7][8]. To our knowledge, this is the first with an IVC thrombus.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Of the 27 identified publications, the authors found 15 published reports of discitis or NVO attributable exclusively to F. nucleatum [5][6][7][8]. To our knowledge, this is the first with an IVC thrombus.…”
Section: Discussionmentioning
confidence: 96%
“…A significant proportion of F . nucleatum -associated NVO cases suggest origins of infection arising from the oropharyngeal, respiratory, or dental routes [ 6 - 9 ]. Dissemination of F .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations